God’s «dark Ground» as a problem of the theologo-philosophical theodicy - Ukhov, Oleksandr (Actual Problems of Mind, 2017)
The author considers the conception of the God’s «dark Ground» formulated by F.W.J. Schelling in the context of the historical development of the theologicophilosophical theodicy. By contrasting the Christian-theological and philosophical views on the problem of human freedom and presence of evil in the world, the author concludes that the problem of the good and the evil can be actualized only within a religious world-view.